Dukungan Keluarga terhadap Keyakinan Sembuh Pasien Tuberkulosis Resisten Obat (TB RO) - Puspitasari, Sepsiana; Winarti R, Sri Arini (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2024)
Patients with drug-resistant tuberculosis (DR-TB) must undergo a heavy and prolonged treatment, which increases the chances of them defaulting on their medication. Family support is considered to help patients boost their treatment motivation. This study aims to examine the tendency of family support towards the healing beliefs of patients with drug-resistant tuberculosis (TB RO). This is a cross-sectional study involving 50 patients with TB RO in the Special Region of Yogyakarta from 2016 to 2020, utilizing a research instrument in the form of a questionnaire. Patients with good family support tend to be confident in their recovery (84%), while 44% of patients with less family support are uncertain about their recovery. Family support may influence patients' recovery beliefs, depending on the emotional conditions they experience.